Evaluation of Antimony Ores Flotation Data by Topographical Isohips Method - G. OZKAN, SAFAK (Asian Journal of Chemistry, 2010)
In this study, batch flotation experiments were performed on representative antimony ore samples from Emirli mines of Odemis region in Turkey. Stibnite mineral was shown to be flotable using different type and amount of reagents, such as collectors and activators. The tests were conducted by use of Denver laboratory type flotation machine and cells whose operating parameters were also controlled. Flotability results of stibnite ores were evaluated by taking some crucial parameters into account, i.e. dosages of collector and activator. Finally, topographical isohips depending on flotation data were constructed to optimize the parameters by using a special software package.